2022
DOI: 10.1021/acs.chemrestox.2c00033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cytotoxicity and Oxidative Stress Induced by the Pyrethroid Bioallethrin in Human Glioblastoma Cells: The Protective Effect of Vitamin E (VE) and Its Underlying Mechanism

Abstract: Bioallethrin belongs to the family of pyrethroid insecticides. Previous studies have shown that bioallethrin affected the function of muscarinic receptor and subsequently induced neurotoxicity in different brain models. Reactive oxygen species (ROS) are generated in the metabolic course of the human body, which can cause human damage when overactivated. However, whether bioallethrin evokes cytotoxicity through ROS signaling and whether the antioxidant Vitamin E (VE) protects these cytotoxic responses in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This quantitative assessment of cellular ROS generation in both Hepa1-6 and HepG2 cells was corroborated using Image J, aligning with the observations made through confocal fluorescence microscopy and inverted microscope imaging. Our research also indicates that vitamin E (VE), as a lipid-soluble ROS scavenger, 13 can effectively alleviate the changes in intracellular ROS levels caused by our formulations. The phospholipid bilayer structure of ad-exos, along with unsaturated fatty acids enriched in lipid core nanoparticles, serves as fuels for fatty acid oxidation in the presence of high levels of ROS.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This quantitative assessment of cellular ROS generation in both Hepa1-6 and HepG2 cells was corroborated using Image J, aligning with the observations made through confocal fluorescence microscopy and inverted microscope imaging. Our research also indicates that vitamin E (VE), as a lipid-soluble ROS scavenger, 13 can effectively alleviate the changes in intracellular ROS levels caused by our formulations. The phospholipid bilayer structure of ad-exos, along with unsaturated fatty acids enriched in lipid core nanoparticles, serves as fuels for fatty acid oxidation in the presence of high levels of ROS.…”
Section: Resultsmentioning
confidence: 69%
“…To integrate self-assembled nano-prodrugs into lipid-rich adipocytes-derived exosomes (ad-exos), the hydrophobic side chains, such as polyunsaturated fatty acids (PUFAs) and vitamin E, are introduced to promote the spontaneous self-assembly of prodrugs into nanoparticles (NPs). 13 In light of the lipid-rich features of ad-exos, hydrophobic triglycerides (TGs) are ideal as assembly blocks and also serve as gates responsive to lipase, ensuring a more site-specific drug release at tumor sites. 14 Hence, we synthesize two lipidic prodrugs to encapsulate both chemotherapeutic and PDT agents into the nano-assembly, concurrently replacing the cores of ad-exos with this configuration: a thioether bond-bridged triglyceride-like prodrug of DTX (referred to DSTG) and a PUFAylation prodrug of protoporphyrin IX (PpIX) (termed PPLA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Feriani et al, (2020) found vitamin E pre-treatment had prevented the pro-atherogenic effect of pyrethroids with decreased plasma and aortic tissue levels of oxidized low-density lipoprotein and the plasma levels of the pro-inflammatory cytokines. Recently, using in-vitro exposure of human glioblastoma cells to pyrethroid, Lin et al, (2022) found pyrethroid-induced cytotoxicity by increasing ROS productions, decreasing reduced glutathione content and regulation of apoptosis-related protein expression levels and detected partial reversal of these effects in cells pretreated with vitamin E.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 470 glioblastoma patients, Mulpur and colleagues found that complementary therapy with vitamin E non-significantly increases mortality [104]. Recently, Lin and colleagues showed that vitamin E could reverse the effect of the cytotoxic drug bioallethrin on human glioblastoma cells by inhibiting OS and endorsing endogenous redox defense pathways, thus obstructing the chemotherapeutic effects of the drug [105]. However, extensive research and clinical studies are required to reveal the exact regulatory role of individual vitamin E isoforms in brain cancer pathways and to use them in disease management.…”
Section: Vitamin Ementioning
confidence: 99%